Heidegger: dualismo sentido-sinsentido del hombre en las dimensiones de la técnica (2008)
This article tries to analyze the ontological-existential compromise thatman acquires when using new technologies, in the light of the Heideggerian’ proposal. This compromise means, on the one hand, the responsibility of forgetting the self in technology, which immerses manin a non-sense; and on the other, the will to open himself to the recognition of the ways in which his “being-in-the-world” manifests. To this end,the perils of technological “instrumentalization” will be presented, basedupon the Heideggerian explanation about the essence of technology.We will present the Heideggerian concepts of anxiety1 and nothingness concepts, with which we will try to conduct the postmodern man towardsthe encounter with his original sense.